The Influence of Coach Leadership Style on Athlete's Training Motivation in Extracurricular Activities - Ahmad Rohimin; Gustiana Mega Anggita (Universitas Negeri Semarang, 2024)
The coach's leadership style has an important role in increasing the enthusiasm and motivation of athletes to follow the training program. Various factors can influence training motivation, one of which is the leadership style approach the coach applies during training. This study aims to determine the dominant leadership style used by the coach, the level of training motivation, and the influence of the coach's leadership style on athlete training motivation at SMANTIR ATHLETIC CLUB. The type and method used in this study is quantitative research. The sample in this study amounted to 10 people using a total sampling technique. Data collection in this study was done by surveying using questionnaires, and data analysis techniques used were simple regression analysis. The results of this study indicate that first, the dominant leadership style applied by the coach is autocratic, with a percentage of 76%. Second, the level of training motivation of SMANTIR ATLETIK CLUB athletes varies quite a lot. Most athletes have a moderate level of motivation with a percentage of 40%, very high 10%, high 20%, low 20%, and deficient 10%. Third, the coach's leadership style affects training motivation with a sig value of 0.03 and a coefficient of determination of 44.5%. The conclusion is that the dominant leadership style applied by the coach is autocratic, the level of training motivation of the majority of athletes is in the moderate category, and the coach's leadership style influences the training motivation of athletes at SMANTIR ATHLETIC CLUB.